USE OF SOFTWARE PROGRAMS AS ZERO Fill HELP IN OVERCOMING THE PROBLEM AROUND HARD DRIVE - Eko Prasetyo Nugroho; Fivtatianti Fivtatianti, Skom, MM (Jurnal Sistem Komputer, 2003)
Zero Fill, is a software tool programs that are designed for hard disk drive specially branded Quantum. This software is a tool programs that function to format the hard drive. Where is the type of format here is the first format or in other words the software to format the hard drive is working under conditions of low- level or commonly referred to as a low- level format. The advantages of this software is able to fix and remove all existing data within the disk, such as files, folders, directories, file table, partition, boot record and the virus if it exists, so that the drive you've experienced the process of Zero Fill, existing data on the disk is not can be recovered.